1974
DOI: 10.1139/v74-003
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of the Reaction of Picryl Chloride with Sodium Methoxide in Methanol

Abstract: Picrylchloride reacts rapidly with methoxide ion in methanol to form a o-complexcontainingmethoxide ion attached to the C-3 position of the picryl chloride. Thermodynamic and kinetic parameterscharacterizing this reaction are presented and compared with corresponding parameters for the analogous reaction of methoxide ion and 2,4,6-trinitroanisole in methanol. Details concerning the much slower formation of the o-complex containing methoxide ion added to the C-l position of picryl chlorideare also presented.Le … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Recent studies have shown that o-complexes with structures 3 and 4 exist when X = CHO (9). As part of a series of kinetic and equilibrium studies of the reactions of nitroaromatic compounds and bases (9)(10)(11) we have investigated the reactions of sulfite ion with picramide, N-methylpicramide, and N,N-dimethylpicramide. We have determined the specific rate constants and activation parameters for the formation of the 1 : 1 o-com~lexes as well as the thermodynamic parameters associated with 1 : 1 and 2 : 1 o-complex formation in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that o-complexes with structures 3 and 4 exist when X = CHO (9). As part of a series of kinetic and equilibrium studies of the reactions of nitroaromatic compounds and bases (9)(10)(11) we have investigated the reactions of sulfite ion with picramide, N-methylpicramide, and N,N-dimethylpicramide. We have determined the specific rate constants and activation parameters for the formation of the 1 : 1 o-com~lexes as well as the thermodynamic parameters associated with 1 : 1 and 2 : 1 o-complex formation in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of o-complexes which are For personal use only. closely analogous to 3 and 4 have been characterized by nmr as well as uv-vis spectroscopy (1)(2)(3)(4)(5)(6)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, there is as yet no unambiguous uv-vis or nmr evidence for the carbanions 5 and 6.…”
mentioning
confidence: 99%
“…Thus the value of K3 for picryl chloride is ca. six times smaller than the value for TNB (the corresponding ratios for reaction with methoxide ions (21) and with hydroxide ions (18,22) are 6.5 and 5. respectively) and this change is due largely to a decrease in the value of k3 while values of k-3 are similar. The value of kl for attack at the 1-position of picryl chloride is ca.…”
Section: Reaction Of Malononitrile Anion With Picry1 Chloridementioning
confidence: 70%
“…[3] for reaction of TNB. However, since here methoxide attack at the 3-position may be neglected (the equilibrium constant is known (21) to have the low value of 2.6 L mol-' ) we obtain eq. [6].…”
Section: Reaction Of Malononitrile Anion With Picry1 Chloridementioning
confidence: 99%